SOURCE LANGUAGE INTERFERENCE WITH TARGET LANGUAGE IN CONFERENCE INTERPRETING - Dailidėnaitė, Alina; Volynec, Julija (Vertimo studijos, 2017)
This article describes an experimental study of lexical interference in simultaneous interpreting from English into Lithuanian and from Lithuanian into English. The paper aims to contribute to the literature on language interference in simultaneous interpreting as well as to identify the influence of lexical interference on directionality and quality of simultaneous interpreting. The experiment was carried out with 6 students working in two directions (from English into Lithuanian and from Lithuanian into English). The paper presents the analysis of the types, frequency and gravity of lexical interference. The results of the study suggest that lexical interference is more common and more detrimental to quality when interpreting into the B language. The results also demonstrate that interpreters experience more difficulties when interpreting word equivalents than phraseological units.